Endovascular repair of abdominal aortic aneurysm in patients physically ineligible for open repair: very long-term follow-up in the EVAR-2 randomized controlled trial - Sweeting,MJ; Patel,R; Powell,JT; Greenhalgh,RM; EVAR,Trial Investigators (Annals of Surgery, 2017)
OBJECTIVE: The aim of the study was to compare long-term total and aneurysm-related mortality in physically frail patients with abdominal aortic aneurysm (AAA) randomized to either early endovascular aneurysm repair (EVAR) or no-intervention. SUMMARY BACKGROUND DATA: EVAR-2 remains the sole randomized trial to identify whether EVAR reduces mortality in patients physically ineligible for open repair. METHODS: Between September 1999 and August 2004, 404 patients from 33 centers in the United Kingdom aged ≥60 years with AAA >5.5cm in diameter were randomized 1:1 using computer-generated sequences of randomly permuted blocks stratified by center to receive either EVAR (197) or no-intervention (207). The primary analysis compared total and aneurysm-related deaths in groups until June 30, 2015 (mean, 12.0 yrs; maximum 14.1 yrs). RESULTS: Mean follow-up until death or censoring was 4.2 years. There were 187 deaths (22.6 per 100 person-yrs) in the EVAR group and 194 (22.1 per 100 person-yrs) in the no-intervention group. By 12 years of follow-up the estimated survival was 5.3% [95% confidence interval (CI), 2.6-9.2] in the EVAR group and 8.5% (95% CI, 5.2-12.9) in the no-intervention group; there was no significant difference in life expectancy between the groups (both 4.2 yrs; P = 0.97). However, overall aneurysm-related mortality was significantly lower in the EVAR group [3.3 deaths per 100 person-yrs compared with 6.5 deaths per 100 person-yrs in the no-intervention group, adjusted hazard ratio 0.55 (95% CI, 0.34-0.91; P = 0.019)]. Patients surviving beyond 8 years were younger, with higher body mass index, estimated glomerular filtration rate, and forced expiratory volume in 1 second. CONCLUSIONS: EVAR does not increase overall life expectancy in patients ineligible for open repair, but can reduce aneurysm-related mortality.